Perception of work–life balance and professional performance among Venezuelan female gastroenterologists: a pioneering study - Dias, Carla (2025)
Introduction: Worldwide, women represent a significant part, and even the majority, of medical personnel, evidencing a global trend towards the feminization of the profession. However, challenges persist in gender equality in leadership and academic roles. Understanding how women endoscopists manage the delicate balance between their demanding careers and personal lives is crucial to ensuring equitable professional environments. Objective: This research thoroughly explored these dynamics, seeking to understand the unique challenges, coping strategies and factors that influence the successful integration of personal and professional life for these specialists. Materials and methods: a survey was designed that addressed aspects of personal life, academic training, incorporating the Maslach Burnout Inventory (MBI) and the adapted MacDonald and MacIntyre job satisfaction scale. Results: The non-probabilistic sample included 202 female endoscopists aged between 29 and 73 years. It was found that those with children perceived difficulties in career advancement and a lack of workplace support during child-rearing. Nevertheless, there were no significant differences between women with and without children in the perception of workplace discrimination, professional advancement opportunities, or specialized training capabilities. A negative relationship was found between age and the perception of burnout. Job satisfaction, in turn, showed no correlation with any personal variables. Conclusion: These results suggest that, while motherhood imposes work-life balance challenges, professional experience may mitigate burnout, regardless of job satisfaction. Support and mentorship policies are required to achieve an inclusive environment.